Relationship between GII.3 norovirus infections and blood group antigens in young children in Tunisia. (September 2015) - Ayouni, S.; Estienney, M.; Sdiri-Loulizi, K.; Ambert-Balay, K.; de Rougemont, A.; Aho, S.; Hammami, S.; Aouni, M.; Guédiche, M.N.; Pothier, P.; Belliot, G.
Abstract: Noroviruses (NoVs) constitute a major cause of gastroenteritis in Tunisia. One hundred and fourteen matched saliva and stool samples were collected from children ( n  = 114) suffering from acute gastroenteritis at the hospital of Monastir during the winter season 2011–2012. For 98 of 114 children, blood samples were collected for secretor genotyping. NoVs were associated with 36.8% ( n  = 42/114) of the gastroenteritis cases. The GII.3 genotype was the most common (69% of all NoVs). For patients who were phenotyped ( n  = 114) for human blood group antigens (HBGAs), the secretor and non-secretor phenotypes represented 79% and 21%, respectively. Of the NoV infections, 83% were detected in all ABO groups. Five GII.3 isolates, one GII.1 isolate and one GII.7 isolate were detected in Lewis-positive non-secretors, confirmed by genotyping of the FUT2 gene. Even though our data showed that GII.3 NoVs could infect non-secretors, no binding was observed with saliva and GII.3 baculovirus-expressed virus-like particles from the same symptomatic non-secretor individual. This suggests that other factors might also participate in NoV attachment in children and newborns.